Development of Smart Point Application in Aerobic Gymnastics Evaluation - Kharunnisa, Fitri; Ilham; Widowati, Atri; Nugraha, Ugi; Irawan, Turino Adi (Journal of Posthumanism, 2025)
This study aims to develop an Android-based Smart Point application as an innovation in the aerobic gymnastics assessment system. The background of this research lies in the judging process, which is still carried out manually using paper-based score sheets, making it prone to errors and inefficiency. The research used the Research and Development (R&D) method with the Borg and Gall model, consisting of ten stages from analysis to product implementation. The research subjects included aerobic gymnastics judges, media experts, and material experts. Research instruments consisted of validation questionnaires and user trials using a Likert scale. The results showed that the Smart Point application achieved a high level of feasibility with material expert validation of 94.60%, media expert 92.85%, and language expert 93.55%. User trials indicated that the application is practical, efficient, and capable of accelerating the scoring recap process by up to 50%. Therefore, the Smart Point application is considered effective in improving objectivity and efficiency in aerobic gymnastics competitions.